2005
DOI: 10.1002/pen.20405
|View full text |Cite
|
Sign up to set email alerts
|

Filmability and properties of compatibilized PA6/LDPE blends

Abstract: Blends of low density polyethylene (LDPE) and polyamide 6 (PA6), compatibilized with an ethylene-acrylic acid copolymer (EAA), either alone or combined with a low molar mass bis-oxazoline compound (PBO), have been processed in film blowing operations and the properties of the films have been investigated. Without of compatibilization, the filmability of the blend was very poor and no significant specimen was collected. As a result of the reactive compatibilization, the blends with EAA and even more with the EA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 24 publications
3
17
0
Order By: Relevance
“…The aim of this work was to study the preparation and the characterization of blends of a sample of high-density polyethylene with polyamide 6 in the presence of an organo-modified montmorillonite and a compatibilizing system already used for other similar systems [22][23][24]. In particular, the aim of the work was to try to find a correlation between the mechanical performance, the morphology and the interactions between the clay and the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of this work was to study the preparation and the characterization of blends of a sample of high-density polyethylene with polyamide 6 in the presence of an organo-modified montmorillonite and a compatibilizing system already used for other similar systems [22][23][24]. In particular, the aim of the work was to try to find a correlation between the mechanical performance, the morphology and the interactions between the clay and the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
“…During the last years, it has been shown that such blends can be efficiently compatibilized with numerous compounds derived from maleic anhydride, acrylic acid, glycidyl methacrylate, oxazoline, etc., grafted onto the polyolefin chain so that hydrogen bonds, or even covalent bonds, can be formed between the two polymers at the blending stage [15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…This is probably due to some compatibilization effect as already stated in several other works. [10,11,13,42] These effects are even more evident when the CP compounds are added. In this case the viscosity is the highest, in particular at low frequencies when the tendency to an yield stress can be observed, especially in the HDPE-based blends (see Figure 3).…”
Section: Resultsmentioning
confidence: 81%
“…Furthermore, as already said, EAA may act as a compatibilizer for this kind of blends as already found elsewhere for the same polymer couple, [10,11,13,42] while CPs may promote either the formation of compatibilizers and/or also chain extension of the polyamide that can contribute to increase the viscosity. [37][38][39][40] As for the more pronounced non-Newtonian behavior, in compatibilized systems the in situ formed copolymers are located at the interface between the two polymers provoking an increased adhesion between the phases.…”
Section: Resultsmentioning
confidence: 96%
“…The presence of free carboxyl groups on the polymer backbone makes it an excellent candidate for several modification reactions. Examples of the use of modified PEAA can be found in the fields of compatibilization, [15][16][17] biomedical applications 18,19 and packaging. 20 Sodium montmorillonite (Na + -MMT) is the most common clay used to prepare PCNs.…”
Section: Introductionmentioning
confidence: 99%